Hydrocarbon Pollution and its Effect on the Environment - Ince, Muharrem; Kaplan Ince, Olcay (IntechOpen, 2019)
This book covers hydrocarbon pollution, measurement techniques for hydrocarbons, risk assessment, and environmental impact. This comprehensive book takes a broad view of the subject and integrates a wide variety of approaches. This book attempts to address the needs of graduate and postgraduate students and other professionals or readers interested in food, soil, water, and air pollution. The aim of this book is to explain and clarify important studies, and compare and develop the new and groundbreaking measurement techniques. Written by leading experts in their respective areas, the book is highly recommended to professionals interested in environmental and human health because it provides specific and comprehensive examples.